ADOLESCENT REPRODUCTIVE HEALTH: THE RELATIONSHIP BETWEEN SEXUAL LITERACY AND SEXUALLY TRANSMITTED DISEASE PREVENTION - Rani Irinericy (Medical Studies and Health Journal (SEHAT), 2025)
Sexually transmitted infections (STIs) represent a significant reproductive health issue among adolescents both globally and in Indonesia, with particularly high prevalence among individuals aged 15–24 years. Adolescent knowledge of STIs remains limited, and previous studies have often overlooked psychosocial and contextual factors that mediate the relationship between sexual literacy and STI prevention behaviors. This study aims to analyze the extent to which sexual literacy influences STI prevention behaviors among adolescents and to identify the mediating roles of attitudes, self-efficacy, and access to sexual health information. This study employed a Systematic Literature Review (SLR) approach based on the PRISMA 2020 guidelines. Data were collected from the Scopus and Web of Science databases, applying inclusion criteria of empirical articles published in English or Indonesian between 2010–2025, focusing on sexual literacy, STI prevention behaviors, and adolescent populations. Data analysis was conducted using thematic coding and thematic synthesis. Findings revealed that sexual literacy significantly influences STI prevention behaviors, including condom use, routine testing, and open communication. Positive attitudes toward sexual health, high self-efficacy in sexual decision-making, and access to accurate information play crucial mediating roles. The study also confirmed the dominant use of the Theory of Planned Behavior (TPB) and the Health Belief Model (HBM) as theoretical frameworks. Sexual literacy, mediated by attitudes, self-efficacy, and access to information, is a strong predictor of STI prevention behaviors among adolescents. These findings provide an empirical foundation for developing more comprehensive and targeted sexual education programs, taking into account psychosocial and contextual factors to enhance the effectiveness of interventions.